2022
DOI: 10.1002/anie.202201318
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Alkali Metal Reduction of 1‐Adamantanol by London Dispersion Effects

Abstract: A series of alkali metal 1‐adamantoxide (OAd1) complexes of formula [M(OAd1)(HOAd1)2], where M=Li, Na or K, were synthesised by reduction of 1‐adamantanol with excess of the alkali metal. The syntheses indicated that only one out of every three HOAd1 molecules was reduced. An X‐ray diffraction study of the sodium derivative shows that the complex features two unreduced HOAd1 donors as well as the reduced alkoxide (OAd1), with the Ad1 fragments clustered together on the same side of the NaO3 plane, contrary to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Lately, these non‐covalent interactions have been found to be a factor towards the stabilization of theoretically calculated intermediates for bimetallic potassium‐aluminyl compounds, [29a,b] exhibiting interesting alkali‐metal‐mediated reactivity [30a,b] . A recent study by Power and co‐workers demonstrated the significance of LDF in the incomplete reduction of 1‐adamantol with alkali metals (Li, Na, and K) [31] . Having a series of group one aluminate structures at our disposal, we sought to quantify the interactions in the unsolvated complexes 1 , 2 , 3 , and 4 into electrostatic and dispersive components.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lately, these non‐covalent interactions have been found to be a factor towards the stabilization of theoretically calculated intermediates for bimetallic potassium‐aluminyl compounds, [29a,b] exhibiting interesting alkali‐metal‐mediated reactivity [30a,b] . A recent study by Power and co‐workers demonstrated the significance of LDF in the incomplete reduction of 1‐adamantol with alkali metals (Li, Na, and K) [31] . Having a series of group one aluminate structures at our disposal, we sought to quantify the interactions in the unsolvated complexes 1 , 2 , 3 , and 4 into electrostatic and dispersive components.…”
Section: Resultsmentioning
confidence: 99%
“…[ 30a , 30b ] A recent study by Power and co‐workers demonstrated the significance of LDF in the incomplete reduction of 1‐adamantol with alkali metals (Li, Na, and K). [31] Having a series of group one aluminate structures at our disposal, we sought to quantify the interactions in the unsolvated complexes 1 , 2 , 3 , and 4 into electrostatic and dispersive components. Attractive dispersion interactions are an important intermediate range class of stabilizing interactions in organometallic complexes.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, our synthetic routes to the anticipated monosubstituted alkali metal 1-adamantoxide (MOAd 1 , M = Li, Na, and K) afforded the three-coordinate species [M­(OAd 1 )­(HOAd 1 ) 2 ] (Figure ). The significance of this result illustrates the first example of LD interactions limiting the reduction potential of alkali metals, despite excess metal being employed. Energy decomposition analysis of this complex showed that the Ad 1 fragments afford significant dispersion stabilization (and are therefore good DED ligands): approximately one-third of the calculated total bonding energies could be assigned to dispersion effects within this molecule.…”
Section: Designing Enhanced Ld Effects In Hydrocarbon Ligandsmentioning
confidence: 99%
“…Interligand LD interactions from close contacts (orange lines) within the first alkali metal reduction-limited complex [Na­(OAd 1 )­(HOAd 1 ) 2 ]. Adapted with permission from ref . Copyright 2022 Wiley-VCH GmbH.…”
Section: Designing Enhanced Ld Effects In Hydrocarbon Ligandsmentioning
confidence: 99%
“…Theoretical studies further suggested that terpenes acting as DED ligands would provide valuable insight into LD effects in molecular complexes, and how structural conformations affect subsequent reactivity. The introduction of DED ligands has allowed the characterization of otherwise non-isolable species, [16][17][18][19][20][21] and DED ligands have also been shown to be important for understanding previously established reactivities, for example in the formation of alkoxides 22 or enzyme-relevant thiourea catalysts. 23 While larger ligands provide kinetic stabilization, many studies have demonstrated the importance of the underpinning LD interactions within these ligand frameworks which also give rise to stabilizing effects.…”
mentioning
confidence: 99%